Dielectric response and density functional theory assessment of fluorinated dicationic pyridinium ionic liquids. Issue 12 (27th October 2022) - Abdel‐Basset, Trob A.; Rezki, Nadjet; Al‐Sodies, Salsabeel A.; Aouad, Mohamed Reda; Bashal, Ali H; Sharfalddin, Abeer A.; Jaremko, Mariusz; Emwas, Abdul‐Hamid; Hagar, Mohamed
Abstract: This study represent the synthesis and electrical conductivity of two focused dicationic pyridinium ionic liquids (DiILs) carrying tetrafluoroborate and/or hexafluorophosphate as counter anion. Thus, the synthesis required quaternization of the pyridine nitrogen atoms first, followed by a metathetical exchange reaction to produce the task‐specific ILs bearing tetrafluoroborate and hexafluorophosphate as counter anions. The resulting DiILs were characterized by NMR and MS spectroscopy. The dielectric constant and the conductivity of the targeted DiILs were analyzed in detail, within a frequency‐range of 1 KHz to 0.3 MHz and a temperature range of 25–100°C. Density functional theoretical (DFT) calculations were also carried out at the base site, B3LYP 6–311 g (d, p), for the Syn /E isomers of the investigated ionic liquids (ILs). We found non‐coplanar molecular geometries with a twist angle of the Schiff base, dependent on the type of counter ion present. The energy levels and differences of the frontier molecular orbitals (FMOs) were also predicted using DFT calculations. The results revealed that the ILs incorporating BF4 − as counter anions showed high HOMO and LUMO values with a higher energy gap, while low FMOs with a lower energy gap were recorded for the derivative encompassing PF6 − counter anions. These findings were used to help explain the dielectric properties of the investigated DiILs. Abstract : We have synthesised bis‐pyridinium ionic liquids containing tetrafluoroborate and/or hexafluorophosphate and investigated their electrical conductivity. Two dicationic ionic liquids (DiILs) were prepared via quaternization of the nitrogen atom in pyridinium followed by a metathetical reaction to give task specific ILs tethering tetrafluoroborate and hexafluorophosphate as counter anions. The resulting DiILs were characterized by NMR and MS spectroscopy. The dielectric constant and the conductivity of the targeted DiILs were analyzed in detail, within a frequency‐range of 1 KHz to 0.3 MHz and a temperature range of 25 to 100°CC. Density functional theoretical (DFT) calculations were carried out at the base site, B3LYP 6‐311g (d, p), for the Syn /E isomers of the investigated ionic liquids. We found non‐coplanar molecular geometries with a twist angle of the Schiff base, dependent on the type of counter ion present. The energy levels and difference of the frontier molecular orbitals FMOs were also predicted using DFT calculations. Whereas the BF4 derivative shows high HOMO and LUMO values with a higher energy gap, the PF6 derivative shows low FMOs with a lower energy gap. These results were used to understand the dielectric properties of the investigated liquids.